MECHANISMS FOR FINANCING COTTON AND TEXTILE CLUSTERS - Fayziev Oybek Raximovich; Zikirov Baxtiyor Ne’matulla og’li; Yo‘ldoshboyev Asadbek Hojiakbar o‘g‘li (Galaxy International Interdisciplinary Research Journal, 2022)
The article provides information and conclusions on the main mechanisms for financing cotton textile clusters and strategic reforms in the framework of the state’s long-term plans.